2019
DOI: 10.3233/ip-180086
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Internet on corruption awareness and corruption incidence in the EU

Abstract: It is obvious that the Internet connection brings several unquestionable benefits to people and society.However, not all of them can be seen at first sight. This study examines the potential effect of Internet usage on corruption awareness as well as experience with corruption and actual reporting of corruption cases. We conducted mainly IV probit and 2SLS regression based on the data from the Eurobarometer survey. We have found that intensity of Internet usage seems to be a significant factor affecting respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
1
4
0
1
Order By: Relevance
“…The results imply that internet usage reduces corruption in developing countries, while internet usage does not affect corruption in developed countries. Hence, this finding on developing countries agrees with the study of [27]- [30], [40] as the studies concluded the significant negative relationship between internet usage and corruption. However, the results on developed countries indicate no impact of internet usage on corruption.…”
Section: The Effect Of Internet Usage On Corruption Prevention and Ea...supporting
confidence: 90%
See 2 more Smart Citations
“…The results imply that internet usage reduces corruption in developing countries, while internet usage does not affect corruption in developed countries. Hence, this finding on developing countries agrees with the study of [27]- [30], [40] as the studies concluded the significant negative relationship between internet usage and corruption. However, the results on developed countries indicate no impact of internet usage on corruption.…”
Section: The Effect Of Internet Usage On Corruption Prevention and Ea...supporting
confidence: 90%
“…In a recent study on Asia and Africa, [19] opined that corruption reduces the tendency to adopt research, innovation, patents and development among lower-middleincome economies. Similarly, a qualitative study on strategies for combating corruption in Nigeria and Iraq established that Nigeria's corruption-fighting institutional strategies are more effective than Iraq's [27].…”
Section: Extortionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initiatives on e-governance may strongly contribute to making public services more effective, strengthening democracy (Von Haldenwang, 2004), reducing corruption (Goel et al, 2012;Hunady, 2019), increasing municipal transparency (Tejedo-Romero & Araujo, 2020), intensifying competition among businesses (West, 2004), and economic growth (West, 2004) as well as improvements to ecological or environmental quality (Haigh & Griffiths, 2008). Twizeyimana and Andersson (2019) summarise public value of e-government into three dimensions: improved public services, improved administration, and improved social value.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu durum daha çok suistimal olayının açığa çıkarılmasına dolayısıyla bir ülkede gerçekleşen suistimal olaylarının daha doğru bir şekilde tahmin edilmesine olumlu etki etmektedir. Avrupa'da internet kullanımının suistimal farkındalığına etkisi üzerine yapılan bir araştırmanın sonuçları, interneti daha sık kullanan işletme çalışanlarının suistimal farkındalığının daha yüksek olduğunu, bu çalışanların maruz kaldığı suistimal olaylarını raporlamada daha gönüllü olduğunu Mayıs 2023, Sayı: 69, Sayfa: 117-134 ve söz konusu suistimal olaylarını raporlama ihtimallerinin diğer çalışanlara göre daha yüksek olduğunu göstermiştir (Hunady, 2019). Buna göre günümüz dünyasında internet, önemli bir suistimal önleme aracı olarak nitelendirilebilir.…”
Section: İşletmelerde Sui̇sti̇mal Farkindaliğinin öNemi̇unclassified